2014
DOI: 10.1155/2014/480956
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events of Massage Therapy in Pain‐Related Conditions: A Systematic Review

Abstract: Pain-related massage, important in traditional Eastern medicine, is increasingly used in the Western world. So the widening acceptance demands continual safety assessment. This review is an evaluation of the frequency and severity of adverse events (AEs) reported mainly for pain-related massage between 2003 and 2013. Relevant all-languages reports in 6 databases were identified and assessed by two coauthors. During the 11-year period, 40 reports of 138 AEs were associated with massage. Author, year of publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…There is a case report of rhabdomyolysis (16) in an elderly gentleman who received an aggressive prolonged session of massage delivered by two therapists, but such severe adverse events are exceedingly rare. (36) Summary Massage may be a helpful adjunct to the overall treatment strategy of patients with chronic pain. In addition to some evidence of a direct, short term impact on pain, it may provide synergistic benefits through reduction in stress associated with a chronic condition.…”
Section: Risksmentioning
confidence: 99%
“…There is a case report of rhabdomyolysis (16) in an elderly gentleman who received an aggressive prolonged session of massage delivered by two therapists, but such severe adverse events are exceedingly rare. (36) Summary Massage may be a helpful adjunct to the overall treatment strategy of patients with chronic pain. In addition to some evidence of a direct, short term impact on pain, it may provide synergistic benefits through reduction in stress associated with a chronic condition.…”
Section: Risksmentioning
confidence: 99%
“…Some of these reviews further specified SMT as cervical, thoracic or lumbar SMT (21 reviews [46, 47, 49, 54, 57, 65, 91, 96, 103, 105, 114, 115, 119, 121, 123, 125127, 134, 136, 150]). Other reviews did not further specify than ‘manipulation’ (10 reviews [36, 66, 7073, 79, 93, 101, 107]), ‘osteopathic manipulative treatment/therapy’ (8 reviews [38, 52, 56, 64, 81, 82, 116, 139]), and ‘chiropractic care/interventions’ (5 reviews [67, 98100, 137]).…”
Section: Resultsmentioning
confidence: 99%
“…Yin et al conducted a systematic review to evaluate the adverse events of massage therapy in pain-related conditions (48). They indicated that disc herniation, soft tissue trauma, neurologic compromise, spinal cord injury, and dissection of the vertebral arteries were the main complications of massage, and spinal manipulation in massage has repeatedly been associated with serious adverse events especially, but the incidence of such events is low.…”
Section: Chinese Massagementioning
confidence: 99%